2002
DOI: 10.1002/cyto.10075
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of numerical chromosome aberrations in meningioma tumors as revealed by fluorescence in situ hybridization using 10 chromosome‐specific probes

Abstract: Objective: Although information on the cytogenetic characteristics of meningioma tumors has accumulated progressively over the past few decades, information on the genetic heterogeneity of meningiomas is still scanty. The aim of the present study was to analyze by interphase fluorescence in situ hybridization (FISH) the incidence of numerical abnormalities for chromosomes 1, 9, 10, 11, 14, 15, 17, 22, X, and Y in a group of 70 consecutive meningioma tumors. Another goal was to establish the potential associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
(32 reference statements)
4
25
1
Order By: Relevance
“…3,6,[13][14][15] The present results showed that MIB-1 labeling index is useful for grading meningiomas, but there is significant overlap. In contrast, FISH analysis of the 1p/19q status clearly distinguished atypical meningioma from low-grade meningioma.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…3,6,[13][14][15] The present results showed that MIB-1 labeling index is useful for grading meningiomas, but there is significant overlap. In contrast, FISH analysis of the 1p/19q status clearly distinguished atypical meningioma from low-grade meningioma.…”
Section: Discussionmentioning
confidence: 50%
“…16) Chromosome 22q deletion and/or mutation of neurofibromatosis type 2 gene (NF2) are most frequently detected as the earliest genetic aberrations and found in meningiomas of all malignancy grades, indicating that inactivation of this gene represents an early event in the pathogenesis of meningiomas. 14,15,19,20) LOH for loci on chromosome 22q and mutations in the NF2 locus probably do not play a role in the development of malignancy in meningiomas. 16) Thus, the assessment of chromosome 22q is not suitable for the alterations associated with progression of meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The female-derived tumor M67 displayed a tumor-specific aberration for clones derived from chromosome X, consistent with heterozygous deletion on this chromosome. Deletions on chromosome X have previously been reported for female-derived meningiomas (29,(37)(38)(39). Thus, in tumors shown in Fig.…”
Section: Resultsmentioning
confidence: 56%